The Effect of Accounting Information Systems, Organizational Commitment and Work Discipline on Employee Performance - Rachmad Gesah Mukti Prabowo; Tiwuk Puji Hariyanti (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to determine and analyze the Accounting Information System on the Performance of SKPD Employees in Surabaya City simultaneously and partially, as well as Organizational Commitment and Work Discipline on Employee Performance in the organization to achieve goals. The object of this research is financial management employees at SKPD in Surabaya City as a subject with a total of 54 respondents. The data used in this research is primary data obtained from employees through the distribution of questionnaires obtained from SKPD offices in Surabaya City. The method of analysis of this research is multiple linear regression analysis with the help of the SPSS statistical program. The results showed that the variables of Accounting Information Systems, Organizational Commitment and Work Discipline simultaneously had a positive and significant effect and partially on the performance of SKPD employees in Surabaya City.